The Kulas family name - Connolly, Shirley Mask (1994)
The Kulas name was one of the first Polish Kashub family names to appear in Canada, with most families arriving between 1859 and the 1890s. Seven Kulas families came from the parish of Lipusz, south of Gdansk, and settled in the town of Renfrew and on farms in Renfrew County. Many Kulas families found now around Ottawa, Renfrew, and Renfrew County in Ontario can trace their Canadian roots back to one of the seven families detailed in this work